The meaning and management of organizational culture : a thesis presented in partial fulfilment of the requirements for the degree of Master of Business Studies in Management at Massey University - Ramsey, Philip Lionel (Massey University, 1985)
A means of providing a Diagnostic Data Base for the management of an organization's culture was developed and tested. The literature on organizational cultures was examined and two models of culture were presented. Shared values were central to both models. An instrument for measuring culture, based on shared values, was developed and tested in three organizations. The data from the instrument was analysed along with interviews with the heads of the organizations. The interviews were analysed using the models presented in the thesis and Vaill's Time-Feeling-Focus model of Purposing by leaders of high-performing systems. The data was able to differentiate between an organization dis-playing a high degree of integration, in terms of values, and the other organizations. It also provided other information which may be useful in the management of culture. There appeared to be a link between one of the models, the data produced by the instrument, and the interviews. The instrument was critiqued and revised. Implications for improving organizational effectiveness were examined and suggestions for futher research recommended.
Page 236 missing from the original copy.
Keywords: Philosophy; Organization